INSTITUTIONAL ACCOUNTING–HOW IT DIFFERS FROM COMMERCIAL ACCOUNTING. - Bruegman, Donald C.; Brighton, Gerald D. (The Accounting Review, 1963)
The article focuses on the differences between commercial and institutional accounting. Increasing importance of the role of higher education in the economy have provided a challenge to all members of the accounting profession. Much of the theoretical knowledge relative to commercial accounting practice must be reassessed when accounting for institutions of higher education. There is truly a separate and distinct set of generally accepted accounting principles for colleges and universities. At the same time, it is interesting to conjecture that as more emphasis is placed on the idea of dollar's worth for each dollar spent by colleges and universities, and with such measurement devices as performance budgeting, these non-profit organizations may be moving toward profit and loss applications. Meanwhile, as large business enterprises become more service oriented, they appear to be assuming trusteeship aspects similar to those in institutional accounting. Just as it may be true that institutional accounting can benefit from commercial accounting, the reverse is equally likely.